2020
DOI: 10.14488/bjopm.2020.005
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid approach development to solving the storage location assignment problem in a picker-to-parts system

Abstract: Goal: This study developed a structured decision model capable of solving the storage location assignment problem (SLAP) in a picker-to-parts system, using multiples key performance indicators (KPIs). Design / Methodology / Approach: A hybrid approach was developed. For that, a Multi-Objective Genetic Algorithm (MOGA) was used considering three fitness functions, but more functions may be considered. Through MOGA it was possible to verify a high number of solutions and reduce it into a Pareto frontier. After t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Fontana et al [14] proposed an innovative hybrid decision model designed to address the Storage Location Assignment Problem (SLAP), amalgamating Multiple Objective Genetic Algorithms (MOGA) with Multi-Criteria Decision Making (MCDM). Results from simulations indicated that the additive-veto model assists decision makers in scrutinizing the Pareto front and incorporating qualitative criteria.…”
Section: A Order Assignment-ga Relatedmentioning
confidence: 99%
“…Fontana et al [14] proposed an innovative hybrid decision model designed to address the Storage Location Assignment Problem (SLAP), amalgamating Multiple Objective Genetic Algorithms (MOGA) with Multi-Criteria Decision Making (MCDM). Results from simulations indicated that the additive-veto model assists decision makers in scrutinizing the Pareto front and incorporating qualitative criteria.…”
Section: A Order Assignment-ga Relatedmentioning
confidence: 99%
“…For businesses, large or small, some conditions affect performance, such as: limits on design because of available space; existence of middle aisles [ 19 ] and wide aisles [ 20 ]; product deterioration while in storage [ 21 ]; accounting for product returns [ 22 ]; safety constraints, such as a minimum distance between the storage locations of two items; convenience constraints, as when two products should be within a certain distance because it is likely that they are ordered together; precedence constraints [ 3 , 23 , 24 ], which impose that certain products should be among the first to be picked, for being heavy, and that others should be among the last to be picked, for being light or fragile; traffic constraints, with one-way aisles in parts of the warehouse; order due time constraints [ 25 , 26 ]; ergonomic considerations [ 27 ] and the risk of infections [ 28 ]. Rigorous, optimal solutions are generally beyond the capabilities of current computers and many publications use heuristic approaches (e.g., [ 29 ]) and/or empirical optimization methods inspired by physical analogies, such as simulated annealing [ 30 ], or biological analogies, such as the genetic algorithm [ 31 – 33 ], ant colony optimization [ 34 – 36 ], and particle swarm optimization [ 11 , 37 ], including the development of hybrid methods [ 38 , 39 ] that use artificial neural networks [ 40 , 41 ] to provide quick answers. There is no guarantee that such algorithms will locate the global minimum of the objective function but computer implementations of several of them are freely available or may be readily coded.…”
Section: Introductionmentioning
confidence: 99%